Fragile watermarking scheme based on SHA-256 hash function and mersenne twister for medical image authentication - Noor Aqilah, Abdul Halim; Ernawan, Ferda; Eh Phon, Danakorn Nincarean; Kohbalan, Moorthy (The World Academy of Research in Science and Engineering, 2020)
Medical images can be easily manipulated by irresponsible persons and the altered medical image can be hard to identify. Fragile watermarking scheme is an alternative solution to authenticate and protect the medical images. Fragile watermarking scheme becomes vulnerable against modification by attackers. This research proposed a fragile watermarking scheme for medical images based onSHA-256 and Mersenne twister. A medical image was split into a region of interest (ROI) and region of non-interest (RONI). The ROI as watermarked image is encrypted by SHA-256 and the result is scrambled by Arnold transform with a secret key before embedding the watermark. The scrambled hash values are randomly embedded into RONI by using Mersenne Twister with a secret key. The experimental results showed that our scheme produces high imperceptibility with PSNR value of about 83 dB. The proposed scheme was able to detect tampers accurately on the medical images. The proposed scheme improved the invisibility of the watermarked image and it provided additional security. The proposed scheme authenticated and validated the originality of the medical images.